Breaking Polymer Chains with Self‐Propelled Light‐Controlled Navigable Hematite Microrobots. (30th April 2021) - Urso, Mario; Ussia, Martina; Pumera, Martin
Abstract: The increasing use of polymers has led to an uncontrollable accumulation of polymer waste in the environment, evidencing the urgent need for effective and definitive strategies to degrade them. Here, self‐propelled light‐powered magnetic field‐navigable hematite/metal Janus microrobots that can actively move, capture, and degrade polymers are presented. Janus microrobots are fabricated by asymmetrically depositing different metals on hematite microspheres prepared by low‐cost and large‐scale chemical synthesis. All microrobots exhibit fuel‐free motion capability, with light‐controlled on/off switching of motion and magnetic field‐controlled directionality. Higher speeds are observed for bimetallic coatings with respect to single metals. This is due to their larger mixed potential difference with hematite as indicated by Tafel measurements. As a model for polymers, the total degradation of high molecular weight polyethylene glycol is demonstrated by matrix‐assisted laser desorption/ionization mass spectrometry. This result is attributed to the active motion of microrobots, enhanced electrostatic capture of polymer chains, improved charge separation at the hematite/metal interface, and catalyzed photo‐Fenton reaction. This work opens the route toward the degradation of polymers and plastics in water using light. Abstract : Novel hematite‐based Janus microrobots are presented, showing self‐propulsion in water under light irradiation and magnetic field‐controlled navigation. Owing to their active motion and catalyzed photo Fenton reaction, these self‐propelled microrobots can on‐the‐fly degrade high molecular weight polyethylene glycol in water. This extends the potential application scope of microrobots to the degradation of polymer and plastic waste, a pressing environmental problem.